(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Ethnomathematics is the new approach that has mathematical education to favor learning in students of different educational levels. It is understood epistemologically as a teaching method that seeks to understand the different ways of knowing different minority cultures during a globalized society. For this reason, the objective was to interpret the experiences of the mathematics teachers of the Santa Clara of Uchunya community of Peru concerning ethnomathematics work. Methodologically, the research was approached from a qualitative perspective, making use of the interpretative paradigm through the ethnomethodological method. This research allowed the recognition of four units of analysis for the presentation of the results: a) Traditional mathematics and ethnomathematics, irreconcilable?; b) Ethnomathematics and knowledge management, fundamental pillars for the rescue of ancestral culture; c) Importance of ethnomathematics in the training process of Aboriginal students; d) Future challenges of ethnomathematics for the achievement of quality and inclusive education in Peru. The interpretation of the findings raises new questions: How can universities manage ethnomathematics training programs to achieve social gaps? Are Peruvian universities ready to transform their curricula and include training in ethnomathematics? What will be the policies of the Peruvian State to reduce social gaps through the implementation of ethnomathematics programs? What will be the educational reality in other Aboriginal populations regarding the perception of ethnomathematics?.